Implementasi Mendongeng pada Mata Pelajaran Bahasa Indonesia untuk Penanaman Karakter Anak Sekolah Dasar - Yohanes Debritto Jurahman (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
Children’s’ fiction story contains moral teachings for character education. Fables are selected for implementation of this research for the reason that they include Indonesian cultural background. The storytelling was performed based on some elements: (a) opening technique, (b) movement exercises, (c) properties, (d) vocal sounds, (e) gestures, (f) sound intonation, (g) expression, and (h) closing techniques. This research aims to examine in depth the implementation of storytelling in Indonesian Language subject for character education. This research uses descriptive qualitative method, gaining sources from elementary school teachers in Wates Subdistrict. The data was collected through in-depth interviewing and observation, validated with triangulation method, that underwent the techniques carried out by data collection, reduction, presentation and verification or conclusion. Based on the interview to the teachers, it is concluded that storytelling can be used to educate characters to elementary school students.